Ethanol supernatant extracts of Gynura procumbens could treat nanodiethylnitrosamine-induced mouse liver cancer by interfering with inflammatory factors for the tumor microenvironment. (1st March 2022) - Zhang, Ting; Gu, Hong-Wei; Gao, Jin-Xing; Li, Yu-Sang; Tang, He-Bin
Abstract: Ethnopharmacological relevance: Gynura procumbens (Lour.) Merr, (Family Asteraceae), which serves as both medicine and food in traditional ethnic medicine, has the effects of diminishing inflammation, relieving cough, reducing blood glucose and lipids levels, mitigating hepatotoxicity, and can be used for liver cancer prevention and treatment. Aim of the study: To explore how the ethanol extract of Gynura procumbens stems (EEGS) can effectively intervene in the tumor microenvironment, it is necessary to study the mechanism of EEGS on the chemical toxicant nanodiethylnitrosamine (nanoDEN) that induces liver cancer. Materials and methods: EEGS contains large quantities of caffeoylquinic acid (CAC) and non-caffeoylquinic acid (n-CAC), which can be separated by high-performance liquid chromatography. The liver cancer model that was induced by the chemical toxin, nanoDEN, was used to clarify the effective mechanism for tumor intervention of the EEGS and its active ingredients. Results: (1) after interventions with the four drugs on liver cancer, the tumor nodules were obviously reduced and inflammation levels improved. (2) The immunohistochemical staining results showed that both the EEGS and its active ingredients could significantly reverse the abnormal changes in inflammation, proliferation, aging and hypoxia-related proteins in mouse liver tissues that were caused by nanoDEN. (3) Real-time PCR results showed that compared with the nanoDEN group, the expression levels of inflammatory, fatty, and fibrosis-related factors in each group after drug intervention were decreased. (4) The transmission electron microscopy measurements showed that the EEGS significantly reversed the nanostructure changes in hepatocytes that were induced by nanoDEN. Conclusion: The EEGS component of Gynura procumbens is effective in preventing and treating liver cancer by interfering with the inflammatory microenvironment during oncogenesis induced by nanoDEN. Graphical abstract: Image 1 Highlights: EEGS have a good effect in the treatment of liver cancer. EEGS contains two major active components, CAC and n-CAC. CAC and n-CAC are effective against liver cancer by interfering with the tumor microenvironment.